Self‐Assembly of Anionic Porphyrins and Alkaline or Alkaline Earth Metal Ions Mediated by Cucurbit[7, 8]uril. Issue 5 (11th February 2013) - Lei, Wanhua; Jiang, Guoyu; Zhou, Qianxiong; Hou, Yuanjun; Zhang, Baowen; Cheng, Xuexin; Wang, Xuesong
Abstract Nanoscaled coordination polymers based on biologically prevalent ions have potential applications in drug delivery and biomedical imaging. Herein, coordination polymer nanoparticles of anionic porphyrins, including meso‐tetra(4‐carboxyphenyl)‐porphyrin (H2TCPP4−) and meso‐tetra(4‐sulfonatophenyl)‐porphyrin (H2TPPS4−), and alkaline or alkaline earth metal cations, such as K+ and Ca2+, were constructed in aqueous solution in the presence of cucurbit[7]uril (CB7) or cucurbit[8]uril (CB8). UV/Vis absorption and fluorescence spectroscopy, dynamic light scattering (DLS), scanning electron spectroscopy (SEM), and atomic force microscopy (AFM) were applied to explore the assembly and particle formation of porphyrin anions and metal cations mediated by CBn. The particle size depends on the kinds of CBn and metal cations and their concentrations. The uptake of H2TPPS4− particles by tumor cells (A549 cells) was found to be more efficient than H2TPPS4− at 37 °C, showing the application potential of such assembled particles in biology and medicine.